Optical Coherence Tomography Angiography for the Evaluation of Retinal Vasculature in Fabry Disease: Our Experience and Review of Current Knowledge - Bacherini, Daniela; Vicini, Giulio; Nicolosi, Cristina; Tanini, Ilaria; Lenzetti, Chiara; Finocchio, Lucia; Cirami, Lino Calogero; Dervishi, Egrina; Rizzo, Stanislao; Virgili, Gianni; Giansanti, Fabrizio; Sodi, Andrea (Frontiers in Neurology, 2021)
Purpose: Optical coherence tomography angiography (OCTA) is an objective and non-invasive tool for the evaluation of the retinal microvascular changes in Fabry disease (FD). We investigated changes in retinal vasculature in FD patients, and the possible correlation with systemic parameters, by using OCTA, and reviewed the current status of literature. Methods: Thirteen FD patients (8 female, 5 males, mean age 49.85±14.7 years) were compared with 13 age- and sex-matched healthy controls. OCTA 3×3 mm macular scans were performed in all subjects. We evaluated the vessel density and vessel perfusion in different macular areas (whole, inner and outer) of both the superficial capillary plexus (SCPVD and SCPVP) and of the deep capillary plexus (DCPVD and DCPVP). We also evaluated foveal avascular zone (FAZ) metrics (area, perimeter and circularity), and correlation between systemic and OCTA parameters. A literature review on the current understanding of OCTA in FD is then presented. Results: FD patients showed significantly lower SCPVD values in the whole area (17.37± 2.08 mm-1 vs. 18.54±1.21 mm-1; p-value 0.022), as well as in the outer area (17.46±210 mm-1 vs. 19.08±1.14 mm-1; p-value 0.002), but no in the inner. Even the DCPVD was significantly lower in all the imaged areas: whole (17.75±3.93 mm-1 vs. 19.71±1.20 mm-1; p-value 0.024), outer (18.25±4.17 mm-1 vs. 20.33 ± 1.20 mm-1; p-value 0.023) and inner (19.54±4.17 mm-1 vs. 21.96±1.55 mm-1; p-value 0.011). There were no significant differences in vessel perfusion parameters (both SCPVP and DCPVP ones) and FAZ. No significant correlations were found between the OCTA parameters and systemic parameters (maximal left ventricular wall thickness and glomerular filtration rate) in FD patients. Conclusions: OCTA can be considered a promising non-invasive tool, which enables a quantitative evaluation of retinal vascular involvement in FD, despite the varying data reported in literature. Our results support the use of OCTA as an objective tool to evaluate retinal vascular abnormalities in FD. The utility of OCTA in FD needs to be validated by longitudinal studies taking into account the overall progression of the disease.